IMPLEMENTATION OF THE PROGRAM OF SOCIAL AND HYGIENE MONITORING OF DRINKING WATER BY THE CENTERS FOR DISEASE CONTROL AND PREVENTION IN THE INDUSTRIAL REGION OF UKRAINE - Зайцев, Вячеслав; Борвінко, Ельвіра (SWorldJournal, 2023)
The work presents the results of research based on the hygienic assessment of laboratory studies of water from a surface water source, as well as drinking tap water consumed by the population of the industrial region of Ukraine, the analysis of cancer in